The microscopic agglutination test (MAT) is an unreliable predictor of infecting Leptospira serovar in Thailand. - Smythe, L; Wuthiekanun, V; Chierakul, W; Suputtamongkol, Y; Tiengrim, S; Dohnt, M; Symonds, M; Slack, A; Apiwattanaporn, A; Chueasuwanchai, S; Day, N; Peacock, S (2009)
A prospective study in Thailand identified 106 patients with culture-proven leptospirosis. The accuracy of the microscopic agglutination test (MAT) in predicting the infecting serovar was evaluated in 78/106 (74%) patients with a diagnostic titer. MAT correctly determined the infecting serovar in 26 cases (33%), indicating that this assay is a poor predictor of infecting serovar in our setting.